2019
DOI: 10.3389/fmars.2018.00510
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions in Sea Otter Research and Management

Abstract: The conservation and management of sea otters has benefited from a dedicated research effort over the past 60 years enabling this species to recover from a few thousand in the early 20th century to about 150,000 today. Continued research to allow full, pre-exploitation recovery and restoration of nearshore ecosystems should focus on at least seven key challenges: (1) Defining sea otter populations at smaller spatial scales that reflect this species' life history and dispersal patterns; (2) Understanding factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 98 publications
(146 reference statements)
0
32
0
Order By: Relevance
“…A first step in achieving this goal is to define the spatial scale at which K is to be measured or estimated. There is growing recognition that sea otter populations are structured at fairly small spatial scales (Bodkin 2015, Davis et al 2019, Tinker et al 2019 a ) because of the limited mobility and high site fidelity of reproductive females (Tarjan and Tinker 2016, Breed et al 2017) and because the abundance of their benthic invertebrate prey varies at small spatial scales and is subject to local depletion (Burt et al 2018). Demographically, K for sea otters is determined at local scales (i.e., over tens of kilometers rather than over hundreds of kilometers), and a regional value of K is better understood as the summation of K over all local habitats.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…A first step in achieving this goal is to define the spatial scale at which K is to be measured or estimated. There is growing recognition that sea otter populations are structured at fairly small spatial scales (Bodkin 2015, Davis et al 2019, Tinker et al 2019 a ) because of the limited mobility and high site fidelity of reproductive females (Tarjan and Tinker 2016, Breed et al 2017) and because the abundance of their benthic invertebrate prey varies at small spatial scales and is subject to local depletion (Burt et al 2018). Demographically, K for sea otters is determined at local scales (i.e., over tens of kilometers rather than over hundreds of kilometers), and a regional value of K is better understood as the summation of K over all local habitats.…”
Section: Figurementioning
confidence: 99%
“…This estimate of K has served as a useful benchmark for coastal resource managers for almost 2 decades; however, a re‐analysis of K for southern sea otters is warranted for several reasons. The single habitat predictor used for the earlier analysis was a relatively simple classification of substrate type (rocky, sandy, mixed), but researchers have reported that sea otter abundance and foraging success are affected by a broader array of environmental features including coastal bathymetry (Thometz et al 2016), kelp canopy cover (Nicholson et al 2018), benthic substrate complexity and composition (Stewart et al 2015, Tinker et al 2017), and ocean productivity (Davis et al 2019). We now understand that estuarine systems may represent important sea otter habitat, distinct from soft‐sediment areas of the outer coast (Hughes et al 2013, Silliman et al 2018).…”
Section: Figurementioning
confidence: 99%
“…Additionally, marine predators provide direct ecosystem services when harvested for 10 human consumption or material use (Smith & Addison 2003, Myers & Worm 2005. Because of 11 their high ecological and socio-economic value, predators are not only depleted in many systems 12 (Heithaus et al 2008), but in some cases reintroduced or conserved via management strategies, 13 such as marine reserves, reintroductions, or legal protections (Halpern 2003, Davis et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The continued investigation of sea otter effects on inshore communities and on commercially valuable species has been identified as an important future direction of research (Davis et al, ). Sea otters are often a point of contention for conservationists and commercial fishermen or local subsistence fishing communities (Davis et al, ). Efforts to correctly monitor the effects of reintroduction to previously extirpated areas will likely be inaccurate without an understanding of the concurrent effect of reintroduction of C. enhydri to invertebrate hosts.…”
Section: Possible Sources Of Significance In the Ecosystemmentioning
confidence: 99%